Impact Electronic Word of Mouth (E-WOM) Against Repurchase Intention With Trust Consumer As Variable Mediation for Lazada Users in Semarang City - Firdaus, Hilda; Firdaus, Firdaus (Economics and Business International Conference Proceeding, 2024)
Study This aim for analyze influence electronic word of mouth (E-WOM) to intention buy repeat with trust consumer as variable mediation on users Lazada Semarang City. Population in study This is Lazada users in Semarang City. Samples obtained totaling 112 people. Retrieval technique sample use technique probability sampling with method purposive sampling with spread questionnaire through google forms. Data is processed with SMART- PLS. The research results obtained shows 4 relationships namely: (1) Electronic word of mouth (E-WOM) has an influence positive and significant to trust consumer.(2) Electronic word of mouth (E-WOM) has an influence positive and significant to intention buy repeat. (3) Trust Consumer influential positive and significant to intention buy repeat. (4) Trust consumer mediate connection between electronic word of mouth (E-WOM) and trust consumer. Share research furthermore recommended for add variations in variables independent used, add coverage of the collection area sample and do comparison with other online shops so that later can compared to the result with study This.